PERSEPSI AUDITOR DAN AUDITEE ATAS PENGGUNAAN FAKTOR-FAKTOR KUALITATIF MATERIALITAS PADA BADAN PEMERIKSA KEUANGAN REPUBLIK INDONESIA - Harsa, Dwinanda; Darsono, Darsono (Diponegoro Journal of Accounting, 2014)
The aims of this research is to examine the perceptions of auditors and auditees on the use of qualitative materiality factors in the context of the formulation audit opinion by BPK RI and to examine the perceptions of auditors and auditees for the consequences that may arise if the qualitative materiality factors implemented by BPK RI.            The population of this study is BPK RI’s auditors in 34 provinces and BPK RI’s auditees in this case the provincial, district and city’s governtment which are represented by the management at BPKD and Inspektorat. Research sampel obtained in this study is 167 BPK RI’s auditors and 32 BPK RI’s auditees as respondent. Respondents were given a questionnaire and asked to respond within five Likert scale. Data were analyzed using non-parametric statistical test Mann-Whitney U-test.            The results indicate that there are differences in the perception on the use of qualitative materiality factors which the auditors tend to agree while the auditees tend neutral. The results showed that the auditors and auditees have the same perception of the use of qualitative materiality will improve the quality of BPK RI’s audit and will generate a positive response from the public related to BPK RI’s Audit, and different perceptions of the use of qualitative materiality will improve the quality of financial reporting.